jurnal konsep dasar evaluasi pembelajaran bahasa arab - ranti sapitiri ranti (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2025)
Arabic Language Learning Evaluation Concept Arabic language learning evaluation has a similar concept to general learning evaluation, but requires more detailed explanation. Through study documentation, this concept explains the theory of learning and Arabic in particular. Research Results 1. Evaluation is the process of determining the quality of objects/activities, while measurement determines quantity. Assessment compares measurement results, and tests provide assignments in the form of questions/commands. 2. The purpose of Arabic language learning evaluation is to measure students' competency achievement (listening, reading, writing) to determine follow-up. 3. Evaluation has four functions: sorting, diagnostics, placement and measurement of success. 4. The scope of evaluation covers three domains: cognitive, affective and psychomotor based on Bloom's taxonomy. The concept of Arabic language learning evaluation provides an overview of the importance of evaluation in improving the quality of learning. The results of this study are expected to help improve understanding of Arabic language learning evaluation.